2021
DOI: 10.1097/ta.0000000000003289
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of low-titer O whole blood resuscitation in a civilian level I trauma center

Abstract: BACKGROUND:Military experience has shown low-titer O whole blood (LTOWB) to be safe and beneficial in the resuscitation of hemorrhaging trauma patients. However, few civilian centers use LTOWB for trauma resuscitation. We evaluated the early experience and safety of a LTOWB program at a level 1 civilian trauma center. METHODS:We retrospectively reviewed our trauma registry from January 2018 to June 2020 for patients admitted in shock (defined as ≥1 of the following: heart rate, >120 beats per minute; systolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The mortality was significantly lower in the military DoDTR population (23% vs 41%, P < 0.001). Military patients who survived had a discharge mean GCS of 14 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, 32 (32.7%) of them had a discharge GCS < 9.…”
Section: Resultsmentioning
confidence: 99%
“…The mortality was significantly lower in the military DoDTR population (23% vs 41%, P < 0.001). Military patients who survived had a discharge mean GCS of 14 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, 32 (32.7%) of them had a discharge GCS < 9.…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective review of a Level 1 Civilian Trauma Center Registry, Kemp Bohan et al (2021) reported no significant difference in 24-hour mortality when comparing WBT to BCT [ 27 ]. Two hundred sixteen patients admitted with hemorrhagic shock receiving blood products prehospital or within 24 hours were grouped into three cohorts receiving either WBT (n=34), BCT (n=95), or WBT plus BCT (n=87).…”
Section: Reviewmentioning
confidence: 99%
“…Two hundred sixteen patients admitted with hemorrhagic shock receiving blood products prehospital or within 24 hours were grouped into three cohorts receiving either WBT (n=34), BCT (n=95), or WBT plus BCT (n=87). There were no significant differences across the three study groups regarding mortality (p=0.45); however, at 30 days and during the hospital stay, mortality was higher in the WBT+BCT cohort vs. the WBT only and BCT groups; however, this was not shown to be statistically significant (p=0.05 and p=0.06, respectively) [ 27 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In both groups, platelets were transfused first followed by plasma alternating with pRBCs. Components transfused 1:1:1 deliver a blood substitute that is anemic, thrombocytopenic and hypocoagulable [ 131 ].…”
Section: Management Of the Polytrauma Victimmentioning
confidence: 99%